Rasyid Ridha’s Reformist Thought and Its Influence on Modern Islamic Discourse in the Middle East: Pemikiran Reformis Rasyid Ridha dan Pengaruhnya terhadap Diskursus Islam Modern di Timur Tengah - Saidun Nisa (Yayasan Insan Cendekia Nusantara, 2025)
Research Background: The emergence of reformist Islamic thought in the early 20th century marked a critical turning point in the intellectual history of the Muslim world. Among the most prominent figures in this movement was Rasyid Ridha, whose ideas significantly shaped the trajectory of modern Islamic discourse in the Middle East. This study aims to examine Ridha’s reformist ideas, particularly his efforts to reconcile Islamic principles with modernity, and to assess their influence on later Islamic thinkers and movements. Methods: Using a qualitative-historical method, a qualitative-historical method with a character study approach. Data was collected from Ridha's primary works, mainly through a study of his writings in al-Manar, and analyzed through a literature review of relevant secondary literature. With this method, the research not only reconstructs Ridha's main ideas but also traces the transformation of his thinking and its influence on the mainstream of modern Islamic thought in the Middle East. Key findings: Muhammad Rasyid Ridha is one of the central figures in the development of modern Islamic thought who was able to provide a critical response to the challenges of modernity, colonialism, and globalization. Contribution: This article contributes to enriching the study of Islamic thought by offering a historical and critical analysis of Rasyid Ridha's intellectual contributions, particularly in three main areas: exegesis, political thought, and responses to globalization. Conclusion: Rasyid Ridha’s reformism served as a pivotal bridge between classical Islamic scholarship and the challenges of the modern world.